Utility-scale solar and public attitudes toward siting: A critical examination of proximity. (15th December 2016) - Carlisle, Juliet E.; Solan, David; Kane, Stephanie L.; Joe, Jeffrey
Abstract: Public opinion polls show that the American public strongly supports the development of large-scale solar power facilities. Yet, often with renewable energy development, when specific developments are proposed, they are met with local opposition. In the past, many scholars relied upon explaining such opposition in terms of a NIMBY (Not In My Backyard). However, NIMBYism is criticized as an overly simple, incorrect, and pejorative characterization of opposition. Yet, while some criticize NIMBY explanations, other research demonstrates that distance indeed matters. Research also demonstrates that place attachment, socio-demographic characteristics, and project-related characteristics also matter. Our study integrates these different factors to better understand the nature of support for large-scale solar developments. Specifically, we consider visual impact of large-scale solar facilities and what effects distance between different types of land and the proposed solar facility might have on public support. Therefore, we examine proximity but not just proximity to one's residence but rather to different types of land. Our data are from a 2013 telephone survey (N = 695) from six Southern Californian counties (Inyo, Kern, Riverside, San Bernardino, San Luis Obispo, and Ventura), selected based on existing and proposed solar developments in those areas and available suitable land. Findings suggest that the visual impact of large-scale solar facilities does matter for support and that preference for buffer sizes, and thus proximity of proposed large-scale solar facilities, do change depending on the type of land being considered.